Barcode clonal tracking of tissue-resident immune cells in rhesus macaque highlights distinct clonal distribution pattern of tissue NK cells - Wu, Chuanfeng; Liang, Jialiu A.; Brenchley, Jason M.; Shin, Taehoon; Fan, Xing; Mortlock, Ryland D.; Abraham, Diana M.; Allan, David S.J.; Thomas, Marvin L.; Hong, So Gun; Dunbar, Cynthia E. (Frontiers in Immunology, 2022)
Tissue resident (TR) immune cells play important roles in facilitating tissue homeostasis, coordinating immune responses against infections and tumors, and maintaining immunological memory. While studies have shown these cells are distinct phenotypically and functionally from cells found in the peripheral blood (PB), the clonal relationship between these populations across tissues has not been comprehensively studied in primates or humans. We utilized autologous transplantation of rhesus macaque hematopoietic stem and progenitor cells containing high diversity barcodes to track the clonal distribution of T, B, myeloid and natural killer (NK) cell populations across tissues, including liver, spleen, lung, and gastrointestinal (GI) tract, in comparison with PB longitudinally post-transplantation, in particular we focused on NK cells which do not contain endogenous clonal markers and have not been previously studied in this context. T cells demonstrated tissue-specific clonal expansions as expected, both overlapping and distinct from blood T cells. In contrast, B and myeloid cells showed a much more homogeneous clonal pattern across various tissues and the blood. The clonal distribution of TR NK was more heterogenous between individual animals. In some animals, as we have previously reported, we observed large PB clonal expansions in mature CD56-CD16+ NK cells. Notably, we found a separate set of highly expanded PB clones in CD16-CD56- (DN) NK subset that were also contributing to TR NK cells in all tissues examined, both in TR CD56-CD16+ and DN populations but absent in CD56+16- TR NK across all tissues analyzed. Additionally, we observed sets of TR NK clones specific to individual tissues such as lung or GI tract and sets of TR NK clones shared across liver and spleen, distinct from other tissues. Combined with prior functional data that suggests NK memory is restricted to liver or other TR NK cells, these clonally expanded TR NK cells may be of interest for future investigation into NK cell tissue immunological memory, with implications for development of NK based immunotherapies and an understanding of NK memory.